Demographic predictors of maturity level between Filipino diocesan and religious major seminarians - Orathinkal, Joseph (Animo Repository, 1994)
This study is an investigation on the relationship between certain demographic variables and maturity of 67 Filipino diocesan and 83 religious major seminarians. The demographic variables were age of entry into the seminary, number of years or regency, educational attainment, and socio-economic status. Maturity was operationally defined as raw scores on 11 out of 18 subcales of the California Psychological Inventory (CPI). A researcher-made personal data sheet was used to gather information with regard to the demographic variables. Through Pearson r, significant positive correlations were found between maturity of diocesan major seminarians and their age of entry into the seminary (p.05), number of years of regency (p.05), and present educational attainment (p.01). For the religious major seminarians, the Pearson r values obtained revealed significant positive correlations between maturity and length of stay in the seminary (p.01), number of years of regency (p.01), and present educational attainment (p.01). The t-test for uncorrelated samples showed no significant difference in maturity between the two groups of seminarians. Stepwise regression identified length of stay in the seminary as the best predictor of maturity for religious seminarians, explaining 23.4 percent of the variance. Present educational attainment was the best predictor of maturity for the diocesans and for the combined group of seminarians, accounting for 9.91 percent and 14.0 percent of the variance, respectively. Findings of this study may be used in evaluating methods of screening seminarians, as well as enhancing seminary formation programs and policies.